1992
DOI: 10.1002/hep.1840160225
|View full text |Cite
|
Sign up to set email alerts
|

Increased 4–Hydroxynonenal Levels in Experimental Alcoholic Liver Disease: Association of Lipid Peroxidation With Liver Fibrogenesis

Abstract: The precise role of lipid peroxidation in the pathogenesis of alcoholic liver disease is still being debated. To explore the issue, this study was undertaken to investigate the status of lipid peroxidation, antioxidants and prooxidants at two discrete stages of experimental alcoholic liver disease. Male Wistar rats were intragastrically fed a high-fat diet plus ethanol for 5 or 16 wk (the duration that resulted in initiation of centrilobular liver necrosis or liver fibrosis, respectively). Lipid peroxidation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
124
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 218 publications
(130 citation statements)
references
References 33 publications
4
124
0
2
Order By: Relevance
“…1,10,11 Ethanol-induced liver damage is believed to be mediated at least in part by increased oxidative stress. 26 A decreased hepatic GSH level is a well-recognized complication of alcoholic liver disease in both humans and animals. [18][19][20][21][22]26 Our study also demonstrated this.…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…1,10,11 Ethanol-induced liver damage is believed to be mediated at least in part by increased oxidative stress. 26 A decreased hepatic GSH level is a well-recognized complication of alcoholic liver disease in both humans and animals. [18][19][20][21][22]26 Our study also demonstrated this.…”
Section: Figmentioning
confidence: 99%
“…26 A decreased hepatic GSH level is a well-recognized complication of alcoholic liver disease in both humans and animals. [18][19][20][21][22]26 Our study also demonstrated this. The steady-state liver GSH level is determined by the rates of its synthesis, utilization (conjugation), and loss (export).…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations